HIGH-PRESSURE PHASE-TRANSITIONS IN THE 6H PEROVSKITES BA3MSB2O9 (M=MG, NI, ZN) - Battle, P; Jones, C; Lightfoot, P; Strange, R (1990)
The 6H perovskitesBa3MSb2O9(M =Mg, Ni, Zn)have been subjected to pressures of up to 5.5 GPa. No structural phase transitions were observed in Ba3MgSb2O9. Ba3NiSb2O9 transformed from a phase containing Sb2O9 dimers formed by face-sharing octahedra into a phase containing NiSbO9 dimers. This was confirmed by a combination of X-ray powder diffraction and EXAFS. Ba3ZnSb2O9 transformed into a cubic perovskite with a partial ordering of zinc and antimony over the octahedral sites. © 1990 Academic Press, Inc. All rights reserved.